1997
DOI: 10.1046/j.1469-8137.1997.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in endophytic fungi from roots and leaves of Lepanthes (Orchidaceae)

Abstract: S U M M A R YLittle is known about non-mycorrhizal endophytic fungi in tropical orchids; still less is known about how endophytes vary within and between individual orchid plants, b'ungal endophytes were isolated from roots and leaves of epiphytic and lithophytic orchids in the genus Lepanthes; seven species, from rainforests in Puerto Rico, were sampled. The endophytes observed most frecjuently were Xylaria species and Rhizoctonia-\'\ke fungi, found in 29 % of roots and 19 % of leaves, and 45 "o of roots and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 25 publications
(41 reference statements)
1
81
0
2
Order By: Relevance
“…Cabral et al 7) showed that epiphytic fungi can sometimes invade the substomatal chambers of living leaves and Petrini 31) speculated that such fungi might be able to enter living leaves of plants under stress. Colletotrichum, Phomopsis, Phyllosticta and Xylaria are ubiquitous forms isolated from a broad range of host plants in the tropics 5,17,30) . In a study on fungal communities of dry thorn and deciduous forest trees in Southern India, Suryanarayanan et al 47) recovered Phyllosticta and Phomopsis as dominant fungi from 20 of 24 host plants studied.…”
Section: Resultsmentioning
confidence: 99%
“…Cabral et al 7) showed that epiphytic fungi can sometimes invade the substomatal chambers of living leaves and Petrini 31) speculated that such fungi might be able to enter living leaves of plants under stress. Colletotrichum, Phomopsis, Phyllosticta and Xylaria are ubiquitous forms isolated from a broad range of host plants in the tropics 5,17,30) . In a study on fungal communities of dry thorn and deciduous forest trees in Southern India, Suryanarayanan et al 47) recovered Phyllosticta and Phomopsis as dominant fungi from 20 of 24 host plants studied.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous reports of pathogenic Colletotrichum spp. that form endophytic and epiphytic associations with plants (2,45,52). Some, such as C. gloeosporioides, C. acutatum, and C. magna, are described as pathogens of one host and asymptomatic endophytes of other species (15,44,48).…”
mentioning
confidence: 99%
“…Other common orders colonizing the roots included Sordariales, Xylariales, and Agaricales. By contributing to drought tolerance and nutrient acquisition, DSF may be integral to the function of arid ecosystems.Symbiotic associations of fungi and plants are ancient and phylogenetically diverse (4,9,11,42,43,60,64,69). Some of these fungi, notably mycorrhizal fungi, have received extensive study, but accumulating evidence indicates that many of the fungi associated with plant roots are dark septate fungi (DSF).…”
mentioning
confidence: 99%